Students’ Elements of Motivation in Joining the EFL Virtual Classroom Using the Zoom Application During the Covid 19 Pandemic - Ahmad Heki Sujiatmoko (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
The students’ motivation in learning has been a crucial issue for many researchers so far. It is because motivation takes an important role to support the students’ learning achievement. Hence, motivation cannot be separated from the teaching and learning activities conducted by the EFL teachers. This current research was aimed at investigating the elements of the students’ motivation in joining the EFL virtual learning activities using the zoom application during the covid 19 pandemic. The research applied a qualitative descriptive approach. To collect the data, the researcher observed one elective class and interviewed some students from the class investigated. The results revealed that the students’ motivation was mostly influenced by the positive effect related to the learning situations created by the teacher when using the zoom application to conduct the teaching and learning activities. This also implied that the zoom application could lead the teachers to think of being creative in conducting the virtual teaching and learning activities.